Analisis Pengaruh Privasi, Keamanan, dan Kepercayaan terhadap Niat Untuk Bertransaksi Secara Online - Shaiful -; Syarifah Hudayah; Saida Zainurossalamia ZA (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2016)
The purpose of this research was to determine and analyze the effect of privacy, security, and trust in the intentions to transactionion online on olx.co.id. Population in this research is the general public Tenggarong Kutai Kartanegara, and the location for this research in Waduk Panji Sukarame. The kind of research used in this study is explanatory research with survey method and total sample in this research is 60 respondent. Sample technique used is obtained by used accidental sampling method. Data sources used primary data and secondary data from literature and internet. Meanwhile data analysis technique used by this research is quantitative analysis with the help of SPSS program that is linear regression analysis. The result of this research indicate that the influence of privacy on the intention to transaction online on olx.co.id negative and no significant, while security positive and significant effect on the intention to transaction, besides confidence positive and significant effect on the irntention to transaction on olx.co.id.Keywords: E-commerce, Privacy, Security, Trust, Transaction Eagerness